Percutaneous Pinning in Displaced Supracondyler Humerus Fracture with Two Crossed K-wires in Children (Journal of Pakistan Orthopaedic Association, 2015)
Objective: To evaluate the result of percutaneous pinning in displaced supracondylar fracture of humerus with two crossed k wires in children and to compare the results with the published literature. Study design: This is a descriptive observational study. Place and duration: This study was conducted at Orthopaedic B unit Lady Reading Hospital Peshawar, from April 2011 to April 2014 on 100 patients with displaced supracondylar fracture of humerus. Material & Methods: One hundred patients with closed supracondylar humerus fractures admitted through emergency were included in this study. Patients above the age of 12 years, open fracture, poly trauma and patients with undisplaced type I fractured were excluded while patients with closed supracondylar humerus type II and III fractures below the age of 12 years were included in the study. All fractures were treated with close reduction and percutaneous pinning with two crossed k wires under general anesthesia. Follow up was done for one year with assessment of radiological healing and clinical outcome that is union, joint movement, deformity and neurovascular injuries.  Results: Among 100 patients 60(60%) were male and 40(40%) female. Left involved in 48 (48%) patients and right in 52 (52%) patients. The mean age at the time of presentation was 6.5 years. Among 100 patients 35 were type II and 65 were type III according to Gartland’s classification. Union was achieved in all patients within 4 to 6 weeks. The mean period of fracture union was 4.8 weeks. All patients got union in an acceptable position. 2 patients (2%) developed compartment syndrome. Pin site infection was the common complication and was noted in 15% patients. No deep infection was noted in these cases, and they were treated with oral anti biotics and dressing. All recovered after removal of pins. Neuropraxia of the ulnar nerve was noted in 2%. No iatrogenic vascular injury was noted. Complete range of movement was achieved after 4 to 6 week. None of the patients developed loss of fixation or cubitus varus deformity. Excellent results were in 60% , good results in 39% patients, poor results in only two (2%) patient. Conclusion: Closed reduction and two cross k wires pinning is a safe and effective method for treating supracondylar fracture of humerus and gives excellent results regarding healing and function.